HEMORRHAGIC COMPLICATIONS ASSOCIATED WITH THE USE OF DIRECT ORAL ANTICOAGULANTS - Sabljić, Nikica; Pantić, Nikola; Trajković, Lazar; Miljić, Predrag; Virijević, Marijana; Bodrožić, Jelena; Pravdić, Zlatko; Cvetković, Mirjana; Suvajdžić-Vuković, Nada; Mitrović, Mirjana (Srpski medicinski časopis Lekarske komore, 2024)
The milestone of treating and preventing venous thromboembolism (VTE) is the application of anticoagulants. For many years the cornerstone was the use of vitamin K antagonists (VKAs), but it was associated with numerous obstacles and complications. With the introduction of a new generation of direct oral anticoagulants (DOAC), some of the difficulties, such as delayed onset/offset of the action, individual dose modifications, inhibition of several coagulation factors, need for frequent monitoring of prothrombin time, multiple drug interactions, have been overcome, while maintaining an adequate safety profile. Therefore, DOACs have rapidly replaced VKAs as a standard of care in the treatment and prevention of VTE, as well as in the prevention of ischemic complications in patients with non-valvular atrial fibrillation. However, the expected consequence of the use of anticoagulant drugs is increased bleeding risk. Several randomized and retrospective studies have analyzed the risk of bleeding associated with the use of DOACs compared to VKAs and between DOACs. It has been clearly shown that intracranial hemorrhage risk is decreased with DOAC compared to VKA, while most studies have shown that the risk of major bleeding is the same or even lower with DOAC. Considering DOAC’s efficacy, excellent safety, and simple application compared with VKAs, it does not surprise their increasingly frequent application in everyday clinical practice. Will VKAs gradually become a part of history, or will their use be limited to a specific, clearly defined population? The time has to show.